The Recent Evolution of Global Tourism: Study Case - Switzerland - Gole, Iulian; Ladaru, Raluca Georgiana; Radulescu, Carmen Valentina; Platagea Gombos, Svetlana (European Journal of Sustainable Development, 2021)
Among other negative economic and health outcomes, the global tourism industry is one of the most affected areas by the recent pandemic. A recent estimation shows that USD 1.3 trillion were lost in revenues, in 2020 only – which represents more than 11 times the loss suffered during the 2009 global economic crisis. It is by far the most the worst year in tourism history. As a direct consequence, many jobs are at risk, especially in small and medium-sized enterprises, in countries where tourism is the main economic component, the situation is quite dramatic. In this paper, we will analyse what happened in world large regions in the sector, what the perspectives to recovery are, and what are the rebound expectations and consumer confidence. We will also investigate the specificity of the tourism situation in Switzerland, where since the beginnings of the pandemic, the big cities and tourist locations have suffered greatly from the absence of foreign tourists. The cities close to the airports showed the strongest decreases in attendance. In contrast, those which are traditionally very touristy were only slightly affected by the decline in the number of foreign visitors.